Avaliação comportamental, neuroquimica e análise in silico do ácido laúrico em modelo de depressao induzida por Corticosterona em camundongos. - Paulo, Manoel Carlito de (2024)
Depression is a mental condition and one of the leading causes of disability worldwide, which is increasingly being discussed by various research fields. It is important to advance research that seeks new substances for the treatment of this disorder. An example is lauric acid (LA), a saturated fatty acid naturally present as the major component of coconut oil. Therefore, the aim of this study was to evaluate the behavioral and neurochemical effects of lauric acid in a depression-like model in mice. Ninety male Swiss mice were divided into five groups: control, corticosterone (Cort), lauric acid (LA 10 and 20mg/kg), and Fluvoxamine. Four groups received corticosterone (20 mg/kg) subcutaneously for 23 days, while the control group received only vehicle (0.9% saline + 0.1% Tween 80) subcutaneously. From the 14th day, the groups received medications: Lauric Acid (LA), fluvoxamine (Flu), or saline+Tween, by gavage 1h after subcutaneous injections. After treatment, mice were subjected to behavioral tests. The behavioral tests performed were forced swimming test (FST), tail suspension test (TST), open field test (OFT), and elevated plus maze test (EPMT). At the end of the tests, the animals were euthanized, and brain areas of the hippocampus, prefrontal cortex, and striatum were removed to evaluate oxidative stress parameters: concentrations of malondialdehyde (MDA), nitrite, and reduced glutathione (GSH). In addition, in silico analyses were performed using a database to identify pharmacological targets for depression and for lauric acid. The targets present in both groups were subjected to protein-protein interaction analysis and molecular docking of the target with LA, using STRING and CB-Docking, respectively. The present study showed that corticosterone administration effectively induced depression-like behavior evidenced by increased immobility time in FST and TST, while only the 20mg/kg dose increased latency in FST, and both doses increased latency in TST. In OFT, there was an increase in crossings in the groups treated with LA, and in EPMT, LA (10 and 20mg/kg) only the lower dose increased entries in the open arms, while both doses increased the time spent in the open arms, also suggesting an anxiolytic effect. Regarding neurochemical parameters, LA reversed the increase in MDA in the hippocampus, prefrontal cortex, and striatum. However, LA reversed nitrite/nitrate levels only in the hippocampus and striatum, but it was not able to elevate reduced glutathione levels. In the in silico analysis, pharmacological targets for depression and LA were identified, which were reduced to 8 common targets. The targets were subjected to docking with LA, showing values between -3.6 and -6.1, thus indicating the effect of LA on the targets. Therefore, it is concluded that lauric acid is a biotechnological alternative as a drug candidatefor depression treatment, as it was effective in altering animal behavior and with activity in antioxidant pathways.